EFEKTIFITAS APLIKASI GOOGLE CLASSROOM PADA PEMBELAJARAN ONLINE TERHADAP HASIL BELAJAR SISWA (STUDI KASUS PADA MATA PELAJARAN GEOGRAFI DI KELAS XI IPA 1 SMA NEGERI 1 TILATANG KAMANG) - Bella Aprillia; Arie Yulfa (JURNAL BUANA, 2021)
This study aims to (1) determine the extent to which the effectiveness of the use of thelearning application Google Classroom in geography learning (2) to determine the extent of the influence of the use of theapplication Google Classroom on the learning outcomes of class XI IPA 1 students of SMA Negeri 1 Tilatang Kamang. This research is descriptive quantitative and the subjects of this research are students of class XI IPA 1 in geography subjects at SMA Negeri 1 Tilatang Kamang. The instruments used in this study included a test instrument consisting of 25 items and a questionnaire instrument consisting of 15 statements and distributed to 29 respondents. The results obtained in this study are (1) The results of the effectiveness analysis obtained are as follows 17.24% are in the effective category, 58.62% are in the moderately effective category, 20.68% are in the ineffective category and 3.44 % are in the very ineffective category. Then the results of the analysis of the effectiveness of google classroom on learning on a student priority scale are 58.62% which is in the "Effective Enough" category, which means that google classroom is quite effective in supporting student learning in class XI IPA 1 at SMA Negeri 1 Tilatang Kamang (2). student learning for 1 semester, it is known that the average daily test results of students as a whole experienced a significant increase.